Moderation of Political Pressure on the Determinants of Audit Quality in the Public Sector: A Study of BPK Auditors for the Maluku and North Sulawesi Regions - Suriana AR Mahdi; N. Nurkholis; Yeney Widya Prihatiningtias; Zaki Baridwan (Australasian Accounting, Business and Finance Journal, 2023)
This study examines audit quality in the public sector. The theory used in this study is quality, which aims to examine political pressure in weakening the influence of independence, integrity, competence, and professionalism on audit quality. The data in this study were taken using a survey by distributing questionnaires to 123 BPK examiners in the Maluku and North Sulawesi regions and analyzed using Moderate regression analysis with Smart PLS 4. The results showed that independence, integrity, competence, and professionalism affected audit quality. In moderation, political pressure has been shown to moderate integrity on audit quality but not as a moderating variable for the effect of independence, competence, and professionalism on audit quality.
Keywords: Independence; Integrity; Competence; Professionalism; Political Pressure; Audit Quality; Indonesia